Nonequilibrium dynamics of quantum fields - Farias, R. L. S.; Cassol-Seewald, N. C.; Krein, G.; Ramos, R. O. (Elsevier B.V., 2007)
The nonequilibrium effective equation of motion for a scalar background field in a thermal bath is studied numerically. This equation emerges from a microscopic quantum field theory derivation and it is suitable to a Langevin simulation on the lattice. Results for both the symmetric and broken phases are presented.
Keywords: nonequilibrium field dynamics; relativistic heavy-ion collisions; lattice simulations